Using cross-functional, cross-firm teams to co-create value: The role of financial measures - Enz, Matias; Lambert, Douglas M. (Elsevier Science B.V., Amsterdam., 2012)
Increasingly, the involvement of representatives from all major business functions in cross-functional, crossfirmteams is being viewed as a means to develop and maintain profitable business-to-business relationships.However, if the measurements of the value co-created in these relationships with customers and suppliers donot incorporate the financial outcomes of joint cross-functional initiatives, managers can be led to makedecisions that jeopardize the long-term profitability of the two firms. In this paper, the authors explore thedifferences in value co-creation when a company is linked to key customers and key suppliers through crossfunctionalteams and when it is not. Using a case study approach, the authors measured value co-creation infinancial terms and describe how managers changed their behaviors toward customers and suppliers whenthey were able to compare the value that was being co-created in each relationship. In each pair ofrelationships, one involved cross-functional teams and the other did not. The results indicate that crossfunctional,cross-firm involvement leads to increased value co-creation. The research suggests that marketingscholars and managers should emphasize the use of cross-functional teams that involve all major functions tomanage relationships with key customers, and should incorporate financial measures in the evaluation ofrelationship performance.